(untitled) (Research, Society and Development, 2021)
Reducing carbon dioxide emissions without affecting the world’s energy supply has made the search for new energy sources an alternative to solve this problem. The reuse of agricultural residues appears as a good alternative. In 2014, Brazil had the capacity to produce approximately 5.5 million coconuts per day, and with this large production, a large amount of waste is also generated. Therefore, this work aims to present a study of the use of residues from coconut agriculture (leaf). A study was proposed for the use of this biomass in in natura form and in the form of gas, obtained through gasification by varying the residence time and the gasification temperature, in order to find the gas with the highest energy conversion yield. After characterization of the samples, it was possible to verify that biomass presents positive results for its use as an alternative source of energy. In the in natura form, the PCI value was 18.96 MJ.kg-1. In gasification, the highest value found was 10.46 MJ.Nm-3.